The distribution and adipogenic potential of perivascular adipose tissue adipocyte progenitors is dependent on sexual dimorphism and vessel location. Issue 19 (12th October 2016) - Contreras, G. Andres; Thelen, Kyan; Ayala‐Lopez, Nadia; Watts, Stephanie W.
Abstract: There are sex associated differences in the risk for cardiovascular comorbidities in obesity and metabolic syndrome. A common clinical finding in these diseases is the expansion of perivascular adipose tissues (PVAT) which is associated with alterations in their role as regulators of vessel function. PVAT hyperplasia and hypertrophy are dependent on the biology of populations of adipocyte progenitor cells (APC). It is currently unclear if PVAT enlargement diverges between males and females and the mechanisms linking APC biology with sexual dimorphism remain poorly understood. This study tested the hypothesis that vessel location and sexual dimorphism affect the distribution and adipogenic capacity of APC in cardiovascular disease risk relevant PVAT sites. PVAT from thoracic aorta (aPVAT) and mesenteric resistance arteries (mPVAT) was collected from 10‐week‐old female and male Sprague–Dawley rats. Differences in APC distribution in stromal vascular fraction cells from PVAT were determined. APC were defined as cells expressing CD34, CD44, and platelet derived growth factor α . In both sexes aPVAT had fewer APC compared to mPVAT and perigonadal adipose tissue (GON). Sex‐related differences were observed in the expression of CD34, where females had fewer CD34 + cells in PVATs. APC proliferation and adipogenic capacity in vitro were not affected by sex. However, APC from aPVAT had a lower proliferation capacity compared to mPVAT. These data demonstrate that the distribution of APC within PVAT exhibits sexual dimorphism and is affected by anatomical location. Abstract : Aortic and mesenteric perivascular adipose tissues exhibit a unique distribution of adipocyte progenitor cells and gene expression signatures that reflect sexual dimorphism and differences due to anatomical location.